Yellowstone for all: creating an immersive, universal design experience at Mammoth Hot Springs - Cross, Rachel A. (Kansas State University, 2020)
National Parks, including Yellowstone, allow people to escape the hustle and bustle of urban life by providing opportunities for peace, restoration, and recreation within a place dedicated to the preservation of natural systems. National Parks are a popular destination as seen in the continual rise of visitation rates. Yellowstone National Park doubled its number of annual visitors from 3.6 million people in 1985 to 7.2 million people in 2015 (National Geographic 2016). Though, as National Parks continue to increase in popularity, visitors with disabilities are not getting a fully immersive experience as compared to those who are non-disabled. In the U.S. approximately 85.3 million or 27.2% of the population has a disability (Taylor 2018). Universal design principles can help create more inclusively designed spaces for all to enjoy, and especially for those with physical mobility, auditory, visual disabilities, neuro-developmental, or neuro-cognitive disorders (Dillon and Green 2019). In Yellowstone National Park, there are several popular tourist areas, including Mammoth Hot Springs, with accessible routes. However, these areas lack necessary elements for providing a fully immersive and inclusive experience. The goal of this projective design research is to illustrate how an immersive, universal visitor experience can be created at Mammoth Hot Springs in Yellowstone National Park. To inform how universal design strategies can be applied at Mammoth Hot Springs, this research first reviews and compares notable federal acts and professional guidelines, including: the Americans with Disabilities Act, the Architectural Barriers Act, the Rehabilitation Act of 1973, ASLA’s Universal Design, the Accessibility Guide to Yellowstone, Programmatic Accessibility Guidelines for National Park Service Interpretive Media, and Visitor Use Management Framework. Next, design precedents from other national, state and public parks are analyzed to learn what effective universal design strategies are being used. Interviews are conducted with subject matter experts, including the accessibility technician of Yellowstone National Park and accessibility coordinator for Grand Teton National Park. Collectively, these findings inform the development of an expanded set of universal design guidelines, specific for use in National Parks. The guidelines are organized into four approaches: accessibility, enrichment, engagement, and multi-sensory experience. To illustrate the application of the expanded design guidelines, a projective site design is created for Mammoth Hot Springs, showing how the site can provide a more immersive and inclusive experience for all.
Keywords: Universal Design; Inclusive Design; Yellowstone National Park; Disabilities